Late-Onset Central Nervous System (CNS) Tuberculosis Presenting as Delirium in a Treated Pulmonary Tuberculosis Patient: A Ceftriaxone and Streptomycin Responsive Case - Vincentius Michael Willianto; Tjipto Wibowo; Zaky Bajamal; Bernadette Dian Novita Dewi (Jurnal Impresi Indonesia, 2025)
Tuberculosis (TB) remains a major health burden in Indonesia. While pulmonary TB is common, extrapulmonary manifestations like tuberculous meningitis (TBM) are severe and diagnostically challenging. Standard oral anti-TB drugs often have poor central nervous system (CNS) penetration, which may lead to treatment failure in the CNS despite pulmonary cure. This study aims to describe a rare presentation of late-onset CNS tuberculosis presenting as delirium shortly after completed pulmonary TB treatment, and to discuss the therapeutic role of ceftriaxone and streptomycin. This study employed a qualitative, single-case report research design to conduct an in-depth investigation into a rare clinical presentation. The study presents the case of a 49-year-old male who developed acute delirium one week after being declared cured of pulmonary TB. Diagnosis was based on clinical presentation, brain MRI showing leptomeningeal enhancement, and cerebrospinal fluid analysis suggestive of TBM, despite a negative GeneXpert test. The patient showed marked neurological improvement after a regimen of intravenous ceftriaxone (2g twice daily) and intramuscular streptomycin (1g daily), without re-instituting standard oral anti-TB drugs. This suggests that the previous oral regimen may have achieved pulmonary cure but failed to eradicate a subclinical CNS infection due to insufficient drug levels. This case highlights the potential for CNS TB reactivation post-pulmonary treatment and suggests that alternative regimens with better CNS penetration, such as ceftriaxone and streptomycin, should be considered. Further studies are needed to evaluate their role as adjunctive therapy for TBM.